Characteristics of competitive activity of qualified basketball with hearing impairment compare to qualified healthy basketball player - I. N. Sobko (Physical Education of Students)
Purpose - the comparison of competitive activity skilled basketball players with normal hearing and impaired hearing aid. The study involved female athletes Ukrainian National Team with hearing (n = 12) and healthy female athletes (n = 12). Technical protocols processed 20 games World Cup, Europe, Ukraine among deaf athletes. Processed records 20 games of the Ukrainian Championship. Found that healthy athletes for the game significantly longer perform and get into the basket fine and three point shots, fewer mistakes, but they are inferior in rebounds. Installed insignificant differences between the number of throws, entering the basket from the middle distance, interceptions in athletes with hearing impairment and healthy athletes. Recommended to increase the coherence of group and team interactions basketball with hearing during the game to use the special visual aids.